2016
DOI: 10.1158/1078-0432.ccr-15-1632
|View full text |Cite|
|
Sign up to set email alerts
|

Flightless I Homolog Represses Prostate Cancer Progression through Targeting Androgen Receptor Signaling

Abstract: Purpose: Flightless I (FLII), member of the gelsolin superfamily of actin-remodeling proteins, functions as a transcriptional coregulator. We aim to evaluate a tumor-suppressive function of FLII in regulating androgen receptor (AR) in prostate cancer progression.Experimental Design: We examined FLII protein and mRNA expression in clinical prostate cancer specimens by immunohistochemistry. Kaplan-Meier analysis was conducted to evaluate the difference in disease-overall survival associated with the expression l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…The lentiviral particles containing GV341-FLAG-YBX1 and GV348-HA-FLII were purchased from Shanghai GeneChem and used to infect cells according to the manufacturer's recommendations. The p-FLAG-YBX1-CSD, p-FLAG-YBX1-C-term, p-HA-FLII-LRR, and p-HA-FLII-GLD plasmids were kindly provided by Professor Chen [22]. Lipofectamine 2000 was used for plasmid transfection as recommended by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The lentiviral particles containing GV341-FLAG-YBX1 and GV348-HA-FLII were purchased from Shanghai GeneChem and used to infect cells according to the manufacturer's recommendations. The p-FLAG-YBX1-CSD, p-FLAG-YBX1-C-term, p-HA-FLII-LRR, and p-HA-FLII-GLD plasmids were kindly provided by Professor Chen [22]. Lipofectamine 2000 was used for plasmid transfection as recommended by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%
“…1a-b. Our previous studies showed that FLII enhanced the sensitivity of CRPC cells to enzalutamide treatment [22]. To explore the mechanism, we reintroduced FLII into C4-2-R, C4-2 and PC-3 cells.…”
Section: Flii Expression Is Negatively Correlated With Pd-l1mentioning
confidence: 99%
See 1 more Smart Citation
“…Tissue samples A collection of 40 different kinds of fresh-frozen prostate cancer tumor specimens and 20 tumor normal adjacent tissues were from Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology. All tumor samples were collected immediately after the surgical removal and snap-frozen in liquid nitrogen [12].…”
Section: Cell Culture Plasmid Construction Reporter Genes Reagentsmentioning
confidence: 99%
“…Moreover, FliI interacts with caspase-11, and recruits it into the Triton X-100 insoluble actin bundle fraction (termed as TI), resulting in the inhibition of inflammasome activation (16,17). Physical interaction of FliI with several transcription factors, including androgen receptor (AR) and carbohydrate responsive element-binding protein (ChREBP), can regulate glucose metabolism and cell proliferation of prostate or colorectal cancer cells via modulation of their transcriptional activities (18,19). Therefore, it is likely that FliI functions differentially through interaction with different binding partners.…”
Section: Introductionmentioning
confidence: 99%